2014
DOI: 10.3749/canmin.1400007
|View full text |Cite
|
Sign up to set email alerts
|

TELLURIDE AND Bi-SULFOSALT MINERALOGY OF THE YANGZHAIYU GOLD DEPOSIT, XIAOQINLING REGION, CENTRAL CHINA

Abstract: The Xiaoqinling vein-style gold district (reserves of >630 t Au) has a very pronounced tellurium signature. The Yangzhaiyu gold deposit is one of the largest gold deposits in this district. The ore-mineral assemblage consists of pyrite, chalcopyrite, galena, bornite, sphalerite, gold, and native tellurium together with a wide variety of telluride and Bi-sulfosalt minerals. The telluride mineral assemblage comprises Phase A, sylvanite [(Au,Ag) 2 Te 4 ], hessite [Ag 2 Te], petzite [Ag 3 AuTe 2 ], calaverite [AuT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 27 publications
(32 reference statements)
2
11
0
1
Order By: Relevance
“…Petzite contains 43.14–43.46 wt% Ag, 21.23–21.56 wt% Au, and 34.92–35.34 wt% Te. Some petzite analyses gave much lower Au contents than ideal petzite (25.4 wt%), which was most likely the result of Au diffusion away from the electron beam during EPMA measurement (Rucklidge & Stumpfl, ; Jian et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Petzite contains 43.14–43.46 wt% Ag, 21.23–21.56 wt% Au, and 34.92–35.34 wt% Te. Some petzite analyses gave much lower Au contents than ideal petzite (25.4 wt%), which was most likely the result of Au diffusion away from the electron beam during EPMA measurement (Rucklidge & Stumpfl, ; Jian et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Except the enrichment of Te in the Songligou gold‐telluride deposit, Te‐rich hydrothermal fluid played an important role in the Xiaoqinling‐Xiong'ershan district from Late Triassic to Early Cretaceous, which indicated that there could be an enriched source of Te in this district. Tellurides were not only found in Late Cretaceous gold deposit, for example, Qiyugou (Shao & Luan, ; Wang et al, ; Han et al, ), Yangzhaiyu (Li et al, ; Jian et al, ), Wenyu (Li et al, ; Zhao et al, ), and Fancha (Li et al, ; Ren, ) gold deposit. Besides, tellurides were also found in the Early Cretaceous Jinduicheng porphyry Mo deposit (Stein, Markey, Morgan, Du, & Sun, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Except the enrichment of Te in the Songligou goldtelluride deposit, Te-rich hydrothermal fluid played an important role in the Xiaoqinling-Xiong'ershan district from Late Triassic to Early Cretaceous, which indicated that there could be an enriched source of Te in this district. Tellurides were not only found in Late Cretaceous gold deposit, for example, Qiyugou (Shao & Luan, 1989;Wang et al, 2001;Han et al, 2007), Yangzhaiyu (Li et al, 2012c;Jian et al, 2014), Wenyu Zhao et al, 2012), and Fancha Ren, 2012) gold F I G U R E 1 7 Gold-bearing quartzpyrite veins cutting across granite porphyry intrusions in the Shangzhuang (a) and Gongyu (b) gold deposits. Abbreviations: Py = Pyrite; Qtz = Quartz deposit.…”
Section: Sources Of Telluriummentioning
confidence: 99%
See 1 more Smart Citation
“…Tellurides of Au, Ag, Pb, and other metals are common trace minerals in gold deposits. The mineralogy, paragenesis, and physicochemical conditions of ore‐forming fluids in telluride‐bearing deposits have been studied intensively (Spry & Thieben, ; Pals & Spry, ; Sung et al, ; Jian et al, ; Xu et al, ; Zhai & Liu, ; Liu et al, ). Telluride melts can scavenge gold from Au‐bearing minerals through coupled dissolution–reprecipitation reactions in hydrothermal fluids even under low temperature conditions (Frost et al, ; Ciobanu et al, ; Cook et al, , b), and these reactions can result in overprinting characters in many gold telluride deposits (Ciobanu et al, ; Cook et al, ; Bi et al, ).…”
Section: Introductionmentioning
confidence: 99%